An ultrafast-response and high-detectivity self-powered perovskite photodetector based on a triazine-derived star-shaped small molecule as a dopant-free hole transporting layer. Issue 24 (1st June 2021) - Shan, Chengwei; Meng, Fei; Yu, Jiahao; Wang, Zhangxia; Li, Wenhui; Fan, Dongyu; Chen, Rui; Ma, Haibo; Li, Gongqiang; Kyaw, Aung Ko Ko
Abstract : A star-shaped small molecule named Triazine-Th-OMeTAD was synthesized and employed as a dopant-free hole transporting layer in an organic–inorganic hybrid perovskite photodetector for ultrafast response and high detectivity in self-power mode. Abstract : Organic–inorganic hybrid perovskites (OIHPs) are becoming appealing for photodetectors due to their excellent optoelectronic properties, but the drawbacks of the commonly used interfacial layers in OIHP photodetectors such as the necessity of doping, high cost and stability issues hinder the further development of this technology. Herein, a star-shaped small molecule with a triazine core unit named Triazine-Th-OMeTAD was synthesized and employed as a dopant-free hole transporting layer in an OIHP photodetector. The Triazine-Th-OMeTAD provided a low-trap-density perovskite film, efficient charge extraction and a large electron injection barrier. As a result, the optimized OIHP photodetector with the Triazine-Th-OMeTAD HTL exhibited a low dark current of 1.09 nA cm −2, a high responsivity of 0.47 A W −1, and a high specific detectivity of over 8.2 × 10 12 Jones at zero bias. Remarkably, a response speed of 18 ns was obtained at a large active area of 11 mm 2 . The high-performance OIHP photodetector demonstrated here acts as a promising candidate for low-cost and high-performance near-ultraviolet-visible photodetection, which is applicable in quick frame rate visible imagers, optical communications and many more.